Modulation of vascular endothelial cells under shear stress on electrospun membranes containing REDV and microRNA-126. Issue 15 (13th October 2021) - Wen, Meiling; Yan, Hongyu; Shi, Xin; Zhao, Yunhui; Wang, Kai; Kong, Deling; Yuan, Xiaoyan
Abstract: For blood vessel regeneration, rapid endothelialization is essential by the effective modulation of vascular endothelial cells (VECs). Herein, microRNA-126 was loaded in electrospun membranes of poly(ethylene glycol)- b -poly(L-lactide- co - ε -caprolactone) combined with REDV peptide to promote VEC growth. The prepared electrospun membranes with suitable mechanical properties in the wet state could accelerate microRNA-126 release to 82.5 ± 4.0% in 56 days. VECs cultured on the electrospun membranes exhibited enhanced adhesion and proliferation with elongating and aligning morphology to the flow direction under shear stress compared with the static culture. The electrospun membranes containing REDV and microRNA-126 could have great potential in applications of bioactive vascular grafts. Graphical Abstract: UF0001